Teaching experience for the training of university students with the use of Flipped Classroom methodology - Fernandez-Alles, Maria Teresa; Sánchez-Jiménez, Miguel Ángel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper focuses on the analysis of university students’ perception of the use of the Flipped Classroom methodology. The results obtained from a teaching experience based on its use will be analysed, focusing, among other aspects, on student satisfaction, understanding of knowledge and acquisition of skills, the degree of involvement of teachers and students, as well as the perceived advantages and disadvantages. The results obtained show, among other benefits, the perception of an improvement in the teaching-learning process and an increase in the quality of training and student satisfaction.